Statistical analysis of carbon and nitrogen sources for growth and sporulation of Exserohilum rostratum causing banana leaf spot disease - Du Ruiqing; Lin Shanhai; Huang Siliang; Zhang Zhengtian; Qin Liping; Li Qiqin (浙江大学学报. 农业与生命科学版, 2015)
Exserohilum rostratum is one of the important pathogens causing banana leaf spots, which has a wide host range. The effects of carbon and nitrogen sources on colony diameters and sporulation among different isolates of E. rostratum have been analyzed using conventional variance analysis method; however, this method was impossible to differentiate the common carbon and nitrogen sources from the species and the isolate-specific ones for growth and sporulation.In-depth difference analyses of various carbon and nitrogen sources were performed to determine the nutritional characteristics of E. rostratum causing banana leaf spot disease, and to provide a basis for disease management.Three isolates (CLER09, D087 and JL05) of the pathogen were used as the experimental ones. The Czapek's medium was used as a basal medium for nutritional tests on carbon and nitrogen sources. The sucrose in the basal medium was substituted with an equal amount of each of the 20 carbon sources tested. The potassium nitrate in the basal medium was substituted with an equal amount of each of the 26 nitrogen sources tested. The basal medium lacking sucrose and that lacking potassium nitrate were used as the controls for carbon and nitrogen utilization tests, respectively. The three isolates were inoculated on the basal media containing different carbon and nitrogen sources at 28℃ for 4 days. The colony diameters and the numbers of conidia produced were separately investigated. The data obtained were evaluated using multiple statistical methods including cluster analysis, discriminatory analysis and comprehensive correlation analysis.The results indicated that the carbon sources had significant effect on growth and sporulation of isolates CLER09, D087 and JL05. Of the carbon sources tested, lactose was identified as the most suitable general carbon source for growth and sporulation of the three isolates. Maltose, sucrose, glucose, α-lactose, xylitol, D-mannose, D-galactose, soluble starch, xylose, L-arabinose, inositol, dextrin and glycerin were identified as the suitable carbon sources for growth and sporulation. Significant correlation was observed between the mean colony diameters and the numbers of conidia produced among the three isolates. Nitrogen sources had significant effects on the numbers of conidia produced, not on the colony diameters. L-cysteine and L-phenylalanine were the most suitable nitrogen sources for growth and sporulation of the three isolates. L-proline and potassium nitrate were identified as the suitable nitrogen sources for growth and sporulation of the three isolates. The isolate CLER09 had the following nutritional characteristics: maltose, α-lactose, D-mannose and dextrin as the carbon sources were suitable for growth and sporulation followed by L-histidine; sucrose as a carbon source was unsuitable for growth and sporulation; significantly positive correlation was observed between the colony diameters and the numbers of conidia produced with reference to the carbon sources; no significantly positive correlation was observed between the colony diameters and the numbers of conidia produced with reference to the nitrogen sources. The isolate D087 had the following nutritional characteristics: D-mannose as a carbon source was unsuitable for growth and sporulation; asparagines, thymine, glutamic acid and vitamin B1 had the secondary suitability as the carbon sources for growth and sporulation; significantly positive correlation was observed between the colony diameters and the numbers of conidia produced with reference to the carbon sources; no significantly positive correlation was observed between the colony diameters and the numbers of conidia produced with reference to the nitrogen sources. Isolate JL05 had the following nutritional characteristics: glucose and trehalose were the most suitable carbon sources for growth and sporulation followed by mannitol; no significantly positive correlation was observed between the colony diameters and the numbers of conidia produced with reference to both carbon and nitrogen sources.In conclusion, general and individual carbon and nitrogen requirements existed among isolates of E. rostratum for growth and sporulation.